Evaluation of Physical Work Environment Measurements to Prevent Occupational Diseases in Agribusiness Industries - Ritwan Agus Prasetyo; Abdul Rohim Tualeka; Yogi Aldias Zakariyah (Universitas Malahayati Lampung, 2026)
ABSTRACT Occupational Safety and Health (OHS) is a fundamental aspect in maintaining industrial productivity and sustainability, particularly in the agribusiness sector, which is at high risk of exposure to physical hazards. This study aims to evaluate the conformity of physical work environment measurements, including noise, Wet Bulb Globe Temperature (WBT), and lighting, with the Threshold Limit Value (TLV) and the requirements of Minister of Manpower Regulation No. 5 of 2018, and to provide control recommendations for the prevention of Occupational diseases. This research method is descriptive qualitative by analyzing secondary data from measurements in 2024–2025 from the accredited laboratory Envilab. The results show that several production areas such as the Buhler Bagging Off and Workshop have noise levels exceeding the TLV of 85 dBA, with values reaching 90 dBA. The WBT and lighting factors also show non-compliance in several areas, although there is a trend of improvement. These findings emphasize the need to improve company compliance with regulations through the implementation of technical and administrative controls, as well as the use of Personal Protective Equipment (PPE). The research conclusion shows that continuous evaluation and regular monitoring of the physical work environment is a strategic step in strengthening the implementation of K3 and preventing the emergence of occupational diseases in the agribusiness industry. Keywords: Physical Work Environment, Noise, Wet Bulb Globe Temperature (WBGT), Lighting, Occupational Diseases.